Maturation of 6S regulatory RNA to a highly elongated structure. (13th October 2015) - Fadouloglou, Vasiliki E.; Lin, Hong‐Tin V.; Tria, Giancarlo; Hernández, Helena; Robinson, Carol V.; Svergun, Dmitri I.; Luisi, Ben F.
Abstract : As bacterial populations leave the exponential growth phase and enter the stationary phase, their patterns of gene expression undergo marked changes. A key effector of this change is 6S RNA, which is a highly conserved regulatory RNA that impedes the transcription of genes associated with exponential growth by forming an inactivating ternary complex with RNA polymerase and sigma factor σ 70 (σ 70 –RNAP). In Escherichia coli, the endoribonuclease RNase E generates 6S RNA by specific cleavage of a precursor that is nearly twice the size of the 58 kDa mature form. We have explored recognition of the precursor by RNase E, and observed that processing is inhibited under conditions of excess substrate. This finding supports a largely distributive mechanism, meaning that each round of catalysis results in enzyme dissociation and re‐binding to the substrate. We show that the precursor molecule and the mature 6S share a structural core dominated by an A‐type helix, indicating that processing is not accompanied by extensive refolding. Both precursor and mature forms of 6S have a highly stable secondary structure, adopt an elongated shape, and show the potential to form dimers under specific conditions; nonetheless, 6S has a high structural plasticity that probably enables it to be structurally adapted upon binding to its cognate protein partners. Analysis of the 6S‐σ 70 –RNAP complex by native mass spectrometry reveals a stable association with a stoichiometry of 1 : 1 : 1. A theoretical 3D model of mature 6S is presented, which is consistent with the experimental data and supports a previously proposed structure with a small stem‐loop inside the central bubble. Abstract : 6S is a regulatory RNA that impedes the transcription of genes associated with exponential growth. In Escherichia coli, the endoribonuclease RNase E generates 6S RNA by specific cleavages of a precursor form. We show that processing by RNase E is inhibited under conditions of excess substrate and that both 6S forms share a structural core dominated by an A‐type helix.